Need to assess the effect of therapy? Ask the patient! - E. Yu. Polishchuk; A. E. Karateev; A. S. Potapova; E. S. Filatova; V. N. Khlaboshchina; V. N. Amirjanova; A. M. Lila (Научно-практическая ревматология)
Achieving a good treatment outcome in rheumatic diseases (RD) requires regular, dynamic patient monitoring and therapy correction if it is not effective or intolerant. The patient assessment must be based on clear criteria to objectify the main manifestations of the disease. For this purpose, the calculation of standard activity and severity indices (DAS28, CDAI, SDAI, BASDAI, ASDAS, DAPSA, PsARC, PASI, etc.) is used. However, this methodology does not always allow the assessment of the fundamentally important parameters of treatment outcome – patient satisfaction and well-being. According to a series of studies, poor therapy satisfaction may be observed in ≈25% of patients with systemic RD who are in remission/low disease activity according to standard indices. Moreover, in 20–30% of cases there is a major discrepancy in the assessment of therapy outcome between the patient and physician. Therefore, a more accurate assessment of the patient’s condition requires, in addition to the calculation of standard indices, the mandatory analysis of patient-reported outcomes – pain, functional impairment, general assessment of disease activity, fatigue, etc. A valuable tool for determining well-being and good therapy outcome from the patient’s point of view is the PASS (“patient acceptable symptom state”). This simple and quite informative index correlates well with core symptoms and indicators of remission/low disease activity. PASS analysis can be used in telemedicine follow-up of patients when an objective examination is not possible. The combined use of PASS and standardized indices can better assess treatment outcomes and improve the quality of life of patients with RD.